Influence of strategic Market Development Practices on Competiveness of Kenyan Tea in the Global market (International Journal of Scientific Research and Management (IJSRM), 2018)
Kenyan tea though acclaimed globally as a high quality product available all year round continues to face growing competition both regionally and globally. This has resulted to a decline in its market share in the global market. The main objective of the study was to examine the influence of strategic market development practices on competiveness of Kenyan Tea in the global market. The study used cross-sectional survey design to collect both qualitative and quantitative data from the respondents. The target population consisted of all one hundred and eighty-nine members of the East Africa Tea Trade Association (EATTA) who participate in the tea auction at Mombasa. The target population was categorized into organizational population and the respondents’ population. Respondents’ population comprised of four top managers from every organization. The sampling frame for this study was seven hundred fifty-six managers who included Chief Executive Officer, Finance Director, Marketing Manager and Operations manager who acted as the major agents of the entire value chain in the tea industry from the producer to the final international consumer. Stratified sampling technique was used to select a sample for buyers, brokers, warehouse, packers and associate members while purposive sampling technique was used to select the managers who represented both the small-scale and large-scale producers. To obtain the desired sample size for the study with the organizational population of 189, Slovin’s formula (1960); n = N/(1+Ne2), was applied. Where; n = Sample Size N = Total Population e = Error of Tolerance with a confidence level of 95 % (giving a margin error of 0.05). The main instrument used to collect primary data from the sampled respondents was structured and unstructured questionnaire. The questionnaire underwent pilot study to test for the validity and reliability of the research instrument. Internal consistency of the questionnaire was determined by use of Cronbach’s Coefficient Alpha (α). Collected data was further prepared for analysis using statistical package for social sciences (SPSS) to generate descriptive and inferential statistics. Data was analysed using percentages, mean and standard deviation while t-tests and p-value was used to test the hypothesis. Pearson correlation coefficient (r) was derived to show the nature and strength of the relationship of the variables where Coefficient of determination (R2) was used to measure the amount of variation in the dependent variable as explained by the independent variable. The study findings indicated that there was a positive relationship between competitiveness of Kenyan tea and strategic market development practices as signified by a coefficient of 0.507. This meant that a 1% change in Strategic Market Development practices increases competitiveness of Kenyan in the global market by 0.507 units. Such increase as revealed by the study was attributed to adoption of market penetration, market segmentation, and market diversification strategies which in the long run created new customers in new segments as well as expansion of the potential market for Kenyan tea in the global market. The study concludes that Market segmentation strategy may be executed in diverse criterion including demographic, geographical, and behavioural segmentation among others. The study emphasized on demographic market segmentation as a strategic market development practice to enhance competitiveness of Kenyan Tea in the global market. The study recommended that to boost competitiveness of Kenyan Tea globally good local and international marketing strategies need to precede the act of exportation. This may be done through organizing consumers into competent consumer associations, promoting market intelligence and branding Kenyan on international markets.